A pragmatic authenticity assessment of lemon (Citrus limon [L.] Burm.f.) juices by its profile of coumarins, psoralens, and polymethoxyflavones. (April 2023) - Jungen, Markus; Dragićević, Nenad; Rodriguez-Werner, Miriam; Schmidt, Simone; Dinis, Katy; Tsamba, Lucie; Jamin, Eric; Fiedler, Thorsten; Fischbach, Nadine; Steingass, Christof B.; Camel, Valérie; Schweiggert, Ralf
Abstract: Coumarins, psoralens, and polymethoxyflavones have long been described as authenticity markers in lemon ( Citrus limon [L.] Burm.f.) juices. However, the lack of quantitative concentration limits for these markers hampers the differentiation of natural variability and acceptable technical process variations from inacceptable lacks in good manufacturing practice (GMP) or even deliberate food fraud by, e.g., the addition of lime ( Citrus  ×  aurantifolia [Christm.] Swingle; Citrus  ×  latifolia [Yu.Tanaka]) juice. In this study, a total of 139 lemon and lime samples, including fruits, juices, juice concentrates, and peel oils from eleven countries and covering all usual processing methods on the market, were analysed using three different liquid chromatographic methods of three different labs. First, we confirmed the considered analytical approaches to yield comparable results and analysed the results in detail per product type and processing technology. After carefully eliminating samples prone to authenticity doubts, we used the remaining dataset (125 samples) for establishing maximum concentration limits for coumarins, psoralens, and polymethoxyflavones for the differentiation of authentic lemon juices produced under GMP conditions, i.e., compliant with the AIJN Code of Practice, from adulterated products made with inacceptable procedures such as excessive co-extraction of flavedo or the admixture of non-lemon Citrus species, particularly lime. Highlights: Citrus authentication is eased by LC-DAD and LC-MS n analysis of coumarins/psoralens/polymethoxyflavones (C/P/PMF). Different LC-DAD and LC-MS n approaches delivered similar results. Peel oil influence on C/P/PMF is negligible for lemon juices produced under GMP. Practical authentication criteria for lemon juice based on C/P/PMF have been proposed.